Optimization and Analysis of a Long-Arm Intelligent Marine Sampling Platform - Heng Zhou; Lejingyi Zhou; Haibo Wu; Minghao Xu; Lindan Zhang; Jia Guo; Wei Fu; Hengchi Zheng; Tian Ni (Journal of Marine Science and Engineering, 2026)
As the core equipment for in situ deep-sea scientific research, the design quality and operational performance of the sampling platform determine the efficiency of deep-sea operations, including long-term continuous observation, high-quality sampling and preservation, and in situ experimental studies. To address technical bottlenecks commonly observed in conventional platforms, including track sinkage, excessive motion drag, and low propulsion efficiency, this study proposes the design and development of a novel sampling platform with tracked-propeller dual-mode propulsion, deployable from either a surface vessel or a large manned submersible, capable of high-throughput, multi-sequence fidelity water sampling, in situ sediment incubation, and seabed mudstone sampling in deep sea. Through hydrodynamic performance analysis and design optimization, both lightweight design and drag reduction were achieved. Furthermore, load verification of the main frame under multiple operating conditions was conducted; results demonstrate that the structure meets strength and stiffness requirements and ensures reliability in typical service environments. This study provides a theoretical basis and technical reference for the development of similar deep-sea sampling platforms and holds substantial engineering application value.